The Influence of Brand Awareness, Brand Image and Brand Equity on Brand Attitude and Its Impact on Interest in Buying Ambon City Motorcycle Brands - Amir Rumra; Noersyam Muhrim (Syntax Corporation Indonesia, 2023)
Currently, marketing aspects no longer focus solely on product functions but are more geared towards brand competition. Successful products or services always have a strong or dominant brand in the market. This research aims to (1) determine the influence of brand awareness, brand image, and brand equity on brand attitude and its impact on the intention to purchase a specific motorcycle brand in Ambon City and (2) identify the differences in brand awareness, brand image, brand equity, and brand attitude for each motorcycle brand, determining which one has a significantly positive influence. The research population consists of respondents who own one of the three brands and respondents interested in purchasing one of the three brands in Ambon City. The sample size was determined using non-probability sampling through purposive sampling, with a total of 300 individuals. The research results indicate that brand awareness, brand image, and brand equity have a significantly positive influence on brand attitude, and brand attitude has a significantly positive impact on the intention to purchase a specific motorcycle in Ambon City. The research also reveals that brand awareness, brand image, and brand attitude for Honda motorcycles are significantly more positive compared to Yamaha and Suzuki, while the brand equity of Yamaha is significantly more positive compared to Honda and Suzuki. The conclusion drawn from this research is that by establishing strong brand awareness, creating a positive brand image, and managing brand equity consistently, consumer attitudes towards the brand can be formed, ultimately driving the purchasing intention of the community towards motorcycle brands in Ambon City.